2019
DOI: 10.1681/asn.2018040362
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin Signaling Results in Integrin β1 Activation

Abstract: BackgroundPatients with certain mutations in the gene encoding the slit diaphragm protein Nephrin fail to develop functional slit diaphragms and display severe proteinuria. Many adult-onset glomerulopathies also feature alterations in Nephrin expression and function. Nephrin signals from the podocyte slit diaphragm to the Actin cytoskeleton by recruiting proteins that can interact with C3G, a guanine nucleotide exchange factor of the small GTPase Rap1. Because Rap activity affects formation of focal adhesions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 65 publications
(135 reference statements)
0
33
0
Order By: Relevance
“…A recent study demonstrated that nephrin signaling results in integrin β1 activation. The finding implied that nephrin-mediated signal regulates podocyte attachment to glomerular basement membrane [98].…”
Section: Slit Diaphragm Functions As a Signaling Platformmentioning
confidence: 90%
“…A recent study demonstrated that nephrin signaling results in integrin β1 activation. The finding implied that nephrin-mediated signal regulates podocyte attachment to glomerular basement membrane [98].…”
Section: Slit Diaphragm Functions As a Signaling Platformmentioning
confidence: 90%
“…Importantly, intracellular actin accumulation quantitatively correlated with perturbed distribution of nephrin in the plasma membrane of fly nephrocytes, which is reminiscent of other nephropathy models in fly. 46 This defect could be linked to a function of cortical actin in the organization of the slit diaphragm 47 or owing to defects in trafficking. The latter notion is supported by our findings on the cessation of organelle mobility during the CaAR reaction 4 and on expression of active INF2 variants.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype is reminiscent of other nephropathy models in fly nephrocytes, such as nephrotic syndrome 28 . The defect in nephrin distribution could either be directly linked to a function of cortical actin in the organization of the slit diaphragm 29 or be due to defects in nephrin trafficking. The latter notion is supported by our findings on the cessation of organelle mobility, which occurs transiently during the CaAR reaction 4…”
Section: Discussionmentioning
confidence: 99%